2020
DOI: 10.1186/s40035-019-0180-x
|View full text |Cite
|
Sign up to set email alerts
|

Replacing what’s lost: a new era of stem cell therapy for Parkinson’s disease

Abstract: BackgroundStem cells hold tremendous promise for regenerative medicine because they can be expanded infinitely, giving rise to large numbers of differentiated cells required for transplantation. Stem cells can be derived from fetal sources, embryonic origins (embryonic stem cells or ESCs) or reprogrammed from adult cell types (induced pluripotent stem cells or iPSCs). One unique property of stem cells is their ability to be directed towards specific cell types of clinical interest, and can mature into function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 59 publications
(96 reference statements)
0
47
0
Order By: Relevance
“…However, none of these are capable of delaying or stopping the progression of the disease. Other promising therapies, some of them yet not tested in humans, have been developed over recent years, including stem cell-based approaches (stem cell and induced pluripotent stem cells derived from patients' fibroblasts have emerged as a powerful tool to obtain a renewable source of dopaminergic neurons that can integrate in the brain [ 560 , 561 ]), the use of neurotrophic factors (e.g., BDNF and GDNF (glial-derived neurotrophic factor)), antioxidants as neuroprotective compounds (e.g., NOS inhibitors, iron chelators, and NRF2 activators [ 438 , 441 , 562 , 563 ]), gene therapy (e.g., viral-gene expression of TH, AADC, or VMAT2 to induce dopamine release, or NURR1 expression which appears to have a neuroprotective role), and immunotherapy (e.g., for the clearance of α -synuclein aggregates) [ 564 567 ]. In addition, another divergent approach is enhancing the autophagy process.…”
Section: Overview and Conclusionmentioning
confidence: 99%
“…However, none of these are capable of delaying or stopping the progression of the disease. Other promising therapies, some of them yet not tested in humans, have been developed over recent years, including stem cell-based approaches (stem cell and induced pluripotent stem cells derived from patients' fibroblasts have emerged as a powerful tool to obtain a renewable source of dopaminergic neurons that can integrate in the brain [ 560 , 561 ]), the use of neurotrophic factors (e.g., BDNF and GDNF (glial-derived neurotrophic factor)), antioxidants as neuroprotective compounds (e.g., NOS inhibitors, iron chelators, and NRF2 activators [ 438 , 441 , 562 , 563 ]), gene therapy (e.g., viral-gene expression of TH, AADC, or VMAT2 to induce dopamine release, or NURR1 expression which appears to have a neuroprotective role), and immunotherapy (e.g., for the clearance of α -synuclein aggregates) [ 564 567 ]. In addition, another divergent approach is enhancing the autophagy process.…”
Section: Overview and Conclusionmentioning
confidence: 99%
“…Generally, stem cells are differentiated into specific nigra A9 DA neurons in large quantities prior to PD transplantation. This step has been thoroughly reviewed by many articles such as in Fan et al (2020) and, thus, will not be further discussed here. However, we focus on developments in technology in cell assessment of differentiated DA neurons.…”
Section: Cell Assessment Of Differentiated Da Neuronsmentioning
confidence: 99%
“…Moreover, common positive markers used to isolate high-quality DA progenitor cells include EN1 and SPRY1 ( Simon et al, 2001 ; Alberi et al, 2004 ; Kirkeby et al, 2017a ); Nurr1 ( Le et al, 1999 ); FOXA2, LMX1B, and MSX1 ( Andersson et al, 2006 ; Chung et al, 2011 ), and the bicoid-related homeodomain factor Ptx3/Pitx3 ( Hargus et al, 2010 ). It is noteworthy that some discrepancies have been found with the requirement for the presence of floor plate-specific cell surface marker CORIN expression ( Ono et al, 2007 ; Chung et al, 2011 ; Kriks et al, 2011 ; Kirkeby et al, 2012 , 2017a ; Doi et al, 2014 ; Arenas et al, 2015 ; Fan et al, 2020 ). A more recent study has identified a cell surface marker integrin-associated protein (IAP, CD47) as a positive marker for FOXA2-positive DA progenitor cells ( Lehnen et al, 2017 ).…”
Section: Cell Assessment Of Differentiated Da Neuronsmentioning
confidence: 99%
“…A number of clinical trials for iPSC-derived products have been initiated for the treatment of neurodegenerative diseases. In Japan, a Phase I/II clinical trial led by Jun Takahashi is currently testing the efficacy of using iPSC-derived dopaminergic progenitor cells to treat Parkinson’s disease [ 110 , 111 ]. In the eye, there are promising results for early trials of RPE replacement therapy, with several ongoing phase I/II clinical trials for PSC-derived RPE replacement [ 112 , 113 , 114 , 115 ].…”
Section: Opportunities For Stem Cell-based Therapies For Regeneratmentioning
confidence: 99%